2002
DOI: 10.1017/s0959270902002204
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of breeding grounds of a Siberian Crane Grus leucogeranus flock that winters in Iran, via satellite telemetry

Abstract: Siberian Crane Grus leucogeranus occurs only in Asia, and is Critically Endangered. The western population of the species has been almost extirpated, wintering at just two known sites, in Iran and India. To help conserve species that migrate long distances it is essential to have a comprehensive conservation plan that includes identification of migration routes and key resting areas. One Siberian Crane was satellite-tracked from the south Caspian Sea to its breeding grounds in Russia during the spring of 1996.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Lagrangian methods, such as individualbased tracking, can be used to better understand variation in migration patterns (Baak et al, 2021), habitat use (Jodice et al, 2015;McCloskey et al, 2018;Phillips et al, 2018), and overlap with threats (Lamb et al, 2018;Isaksson et al, 2021). Tracking has identified previously unknown breeding areas (Kanai et al, 2002) and demonstrated links with distant colonies with seabirds using the nGoM (Montevecchi et al, 2012). Such information could inform population monitoring or recovery efforts and direct them towards the colonies and populations known to use the nGoM.…”
Section: Uncertaintymentioning
confidence: 99%
“…Lagrangian methods, such as individualbased tracking, can be used to better understand variation in migration patterns (Baak et al, 2021), habitat use (Jodice et al, 2015;McCloskey et al, 2018;Phillips et al, 2018), and overlap with threats (Lamb et al, 2018;Isaksson et al, 2021). Tracking has identified previously unknown breeding areas (Kanai et al, 2002) and demonstrated links with distant colonies with seabirds using the nGoM (Montevecchi et al, 2012). Such information could inform population monitoring or recovery efforts and direct them towards the colonies and populations known to use the nGoM.…”
Section: Uncertaintymentioning
confidence: 99%
“…Surveys typically use point counts, transects, or newer technologies such as audio recording units or camera trapping to map the occurrence of a species within a focal area (Beirne et al 2017, Cooper et al 2019, Ortega-Alvarez et al 2020, Schroeder & McRae 2020. The range of a species can also be refined based on data obtained from individual tracking efforts, which may also be used to locate previously unidentified or remote breeding or nonbreeding areas (Kanai et al 2002, McCloskey et al 2018, determine residency time within an area, or identify interactions of individuals with conservation threats (Jodice et al 2015, Lamb et al 2018, Phillips et al 2018. More recently, citizen-science data, such as eBird (www.ebird.org), have been used to assist in delimitation of the geographic range of a species by providing unique sightings (Cooper et al 2019).…”
Section: Open Pen Access Ccessmentioning
confidence: 99%
“…In seabirds, tracking is commonly initiated on individuals captured at nest sites and subsequently used to map migratory paths or locate core use areas. However, tracking has also been used to attempt to locate unknown nesting areas of species captured on non-breeding grounds (Kanai et al 2002, Rayner et al 2020). Remote tracking technology is particularly well suited for seabirds captured at sea when there is no a priori assumption of possible nesting grounds, or when the potential nesting range is too broad (Rayner et al 2015, Rayner et al 2020).…”
Section: Introductionmentioning
confidence: 99%